Crisp-fuzzy representation of Allen's temporal logic - Nor Azlinayati Abdul Manaf,; M. Reza Beikzadeh, (ACTA Press Anaheim, CA, USA, 2007)
Allen's interval algebra is a powerful tool in reasoning temporal knowledge. At any moment of time, one and only one of the thirteen possible relations of Allen's interval algebra can exist between two intervals. However the disjunction relation between two intervals is only represented in terms of qualitative information. It is very hard to determine the degree of each relation. In this paper we introduce a new approach to model the uncertain information of Allen's temporal interval relations. This model adapts the concept of fuzzy set into the classical Allen's Temporal Logic (ATL) that is powerful enough to express the imprecise relations between the temporal intervals. The classical temporal network has been extended to accommodate the CriFuzz-ATL model.